2018
DOI: 10.1103/physrevlett.121.145002
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field Generation in Plasma Waves Driven by Copropagating Intense Twisted Lasers

Abstract: We present a new magnetic field generation mechanism in underdense plasmas driven by the beating of two, co-propagating, Laguerre-Gaussian (LG) orbital angular momentum (OAM) laser pulses with different frequencies and also different twist indices. The resulting twisted ponderomotive force drives up an electron plasma wave with a helical rotating structure. To second order, there is a nonlinear rotating current leading to the onset of an intense, static axial magnetic field, which persists over a long time in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 31 publications
(58 reference statements)
2
55
0
Order By: Relevance
“…The resulting field structure is significantly more complex than the field described in Ref. 9 , we also present numerical results which match the theoretical predictions made here.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…The resulting field structure is significantly more complex than the field described in Ref. 9 , we also present numerical results which match the theoretical predictions made here.…”
Section: Introductionsupporting
confidence: 81%
“…This phenomenon was previously observed in simulations described in Ref. 9 where two co-propagating OAM laser pulses with differing angular mode, frequency, and wavelength are injected into a plasma and couple with an OAM plasmon. The resulting plasmon is shown to generate a second-order quasi-static magnetic field.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Nuter et al proposed that the combination of strong radial and longitudinal electric fields present in tightly focused radial laser beams can transfer angular momentum to electrons through a dissipationless, optical process, resulting in 100-T magnetic fields [21]. Shi et al have demonstrated that two copropagating vortex beams with different frequencies and topological charge produce a twisted ponderomotive force, leaving behind a solenoidal current and quasistatic magnetic field up to 40 T [22].Although these would be powerful new techniques for charged beam collimation, they each rely on laser modes * msederbe@uottawa.ca…”
mentioning
confidence: 99%
“…Although the generation of plasma AM is claimed to originate from the torque of the generated vortex beam [14], the exact dynamics that cause the plasma AM are still unclear. However, a plasma with huge AM has great potential in generating very strong longitudinal magnetic fields [33][34][35][36], and may bring insight into laboratory astrophysics [37]. Therefore, an investigation into the evolution of plasma AM during vortex pulse generation is necessary.…”
Section: Introductionmentioning
confidence: 99%